2019
DOI: 10.2174/1573397114666180717145745
|View full text |Cite
|
Sign up to set email alerts
|

Metformin one in a Million Efficient Medicines for Rheumatoid Arthritis Complications: Inflammation, Osteoblastogenesis, Cardiovascular Disease, Malignancies

Abstract: Metformin effect on AMPK and mTOR pathways gives the capability to changes Treg/Th17 balance and decrease Th17 differentiation and inflammation, osteoclastogenesis and cancers in RA patients. Metformin can be useful in protecting bones especially in first stages of RA and it can decrease inflammation, CVD and cancer in RA patients so Metformin beside DAMARs can be useful in increasing RA patients' life quality with the less harm and cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 78 publications
1
15
0
Order By: Relevance
“…The findings of this study showed that the incidence of CAD, the number of involved vessels, and the impairment of cardiac pacemaker function were higher in patients with DM (15). Our results are in line with previous non-DM patients and in a study of a large group of patients, the patients also showed a higher prevalence of the threevessel disease among DM patients (16).…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this study showed that the incidence of CAD, the number of involved vessels, and the impairment of cardiac pacemaker function were higher in patients with DM (15). Our results are in line with previous non-DM patients and in a study of a large group of patients, the patients also showed a higher prevalence of the threevessel disease among DM patients (16).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, it may also be effective in a number of other applications, such as treating cancer, obesity, nonalcoholic fatty liver disease (NAFLD), polycystic ovary syndrome (PCOS), and metabolic syndrome [ 4 ]. Furthermore, antiaging and bone-protective effects, especially in the first stages of rheumatic arthritis (RA), have also been shown very recently [ 6 , 7 ]. Emerging evidence suggests metformin may have many other benefits, including reducing endoplasmic reticulum (ER) and oxidative stress, as well as anti-inflammatory properties [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…An observational study on data from a Taiwan National Health Insurance Research Database found that patients with RA and T2DM under Cyclooxygenase (COX)-2 inhibitor and metformin had lower admission rates than those on COX-2 inhibitors alone [32]. Finally, a recent review strengthened metformin's multiple benefits in RA patients not only in terms of joint involvement but also affecting other frequently associated illnesses such as cardiovascular disease and cancer [70].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%